Current Research Status of Active-Assist Lower Limb Rehabilitation Exoskeleton Robots - Guo Yifeng; Deng Kai; Huang Limin; He Min; Zhang Min (Jixie chuandong)
It is crucial to develop active assistant lower limb rehabilitation exoskeleton robots in light of the current situation of population aging and the sharp rise in the number of people with lower limb disorders. The current state of research on active assistant lower limb rehabilitation exoskeleton robots was reviewed in this study, both domestically and internationally; single-joint and multi-joint robots were the basis for classification; the structures, applicable populations, application scenarios, and other pertinent details of these two types of robots were particularly summarized. The main technologies were explained and analyzed (actuator type, human-machine doubling, energy and power, etc.). Finally, an analysis and prospect was conducted about the essential technologies and future development trends of active assistant lower limb rehabilitation exoskeleton robots.